2005
DOI: 10.1002/adma.200401169
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured TiO2 Films with 2 eV Optical Gap

Abstract: product, yielding phenylene-modified hybrid mesoporous ethenylenesilica (Ph-HME). The Ph-HME was then sulfonated by heating at 80 C for 3 days in concentrated H 2 SO 4 . The solid was recovered and washed in water at 80 C for 6 h. The washing treatment was repeated twice, and the final product was dried at room temperature to afford Ph±SO 3 H HME.Acid-Catalyzed Reaction: The esterification of acetic acid and pinacol±pinacolone rearrangement were employed as test reactions to examine the acid properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 25 publications
3
92
1
1
Order By: Relevance
“…18,19 The nature of C-induced changes to the TiO 2 electronic band structure is controversial. Both band gap narrowing 20 and the formation of localized midgap states 21 have been proposed to account for the red shift of the optical absorption edge. The codoping of TiO 2 with C and N by Chen et al 22 using the sol-gel technique was also found to further enhance the photo-activity of TiO 2 towards visible light.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The nature of C-induced changes to the TiO 2 electronic band structure is controversial. Both band gap narrowing 20 and the formation of localized midgap states 21 have been proposed to account for the red shift of the optical absorption edge. The codoping of TiO 2 with C and N by Chen et al 22 using the sol-gel technique was also found to further enhance the photo-activity of TiO 2 towards visible light.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of C-induced modifications to the TiO 2 electronic band structure is controversial. Both band gap narrowing [27] and the formation of localized mid-gap states [28] have been proposed for the red-shift of the optical absorption edge. In addition, Sn-doped TiO 2 has also attracted much attention, with Sn-doped rutile TiO 2 reported to lead to a red-shift of the optical absorption edge [29], while other results indicate blue-shifting in Sn-doped anatase [30]; these experimental observations have been confirmed by our previous theoretical studies [31].…”
Section: Introductionmentioning
confidence: 99%
“…16 C-doped TiO 2 , synthesized by flame pyrolysis of Ti sheets in a natural gas flame, displayed a lower band-gap than titania (2.32 versus 3.00 eV). 17 Even if there are several works in the literature focused on C-doped titania, [17][18][19][20] and on doped TiO 2 by the ion-implantation process, 2,6,10,11,14 there is not, to our knowledge, any study on the effects of C doping by ion implantation. The advantage of the ion-implantation process is the outstanding control and repeatability of the implanted fluence and energy.…”
Section: Introductionmentioning
confidence: 99%